PENGARUH LEVERAGE, GROWTH, PROFITABILITAS, DAN LIKUIDITAS TERHADAP NILAI PERUSAHAAN DI BEI - Malvin Ibrahim, Jonnardi (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to obtain empirical evidence about the effects of leverage, growth, profitability, and liquidity towards firm value in manufacturing industries sector basic industries and chemicals listed in Indonesian Stock Exchange during the period of 2014-2018. This research used 48 samples of manufacturing companies that have been previously selected using purposive sampling method for three years. The data used were secondary data in the form of financial information from the financial statements and annual reports. This research data was processed using EViews 9. The result of this research shows that leverage, growth, profitability, and liquidity , does not have a significant effect on firm value. Suggestions that can be given is for further research, it is expected to use other independent variables such as investment opportunity, sales growth, earnings per share (EPS), free cash flow, andbusiness risk that might show better results.